Experimental study of the bed morphology downstream of a sluice gate - Carvalho, L. (2018)
This work describes an experimental study based on a simplified model of a vertical sluice gate installed in a channel with a moving bed of glass spheres with 2 mm diameter. The originated scour cavity and downstream dune were studied. The influence of the apron length and the downstream tailwater depth were also analysed. Imaging techniques provided the tools to this investigation. The data acquisition and processing consisted in acquiring images of the flow and automatically process them to identify the water-sediments interface and the longitudinal profile of sediments? bed at different instants.